Tetanus: A report of two cases and review of literature – A continuing threat to the elderly in Japan - Tsutomu Sugiura; Kazuhiko Yamamoto; Masatoshi Sato; Tadaaki Kirita (Contemporary Clinical Dentistry, 2017)
Tetanus has become rare in industrialized countries, largely due to the effectiveness of immunization. However, the elderly are susceptible to tetanus because many have not received primary immunization; the incidence of tetanus in Japan is still 120 cases/year. The initial symptoms of tetanus, such as trismus and dysphagia, are observed in the orofacial region. However, because of the disease's rarity, the clinician may be unfamiliar with the clinical presentation and may not suspect tetanus. We report two cases of elderly patients with generalized tetanus. Both patients presented trismus and/or dysphagia and consulted three different departments before the diagnosis of tetanus. Japanese clinicians will encounter tetanus more frequently than practitioners in other countries. Dental surgeons should be familiar with the clinical appearance of tetanus and should consider this disease in a nonimmunized patient presenting as an atypical case of trismus and dysphagia.